Association between child marriage and institutional delivery care services use in Bangladesh: intersections between education and place of residence. (June 2019) - Uddin, J.; Pulok, M.H.; Johnson, R.B.; Rana, J.; Baker, E.
Abstract: Objectives: To examine the association between child marriage and women's use of institutional delivery care services and whether education and place of residence moderate this association. Study design: The study used de-identified data from four rounds (2004, 2007, 2011, and 2014) of the Bangladesh Demographic and Health Survey (BDHS). The BDHS is a cross-sectional survey conducted every three years. The analysis was based on 16, 099 ever-married women aged 15–49 years with at least one live birth in the three years before the survey. Methods: The study used multivariable logistic regression models with interaction terms between age at marriage, education, and place of residence. Adjusted predicted probabilities of outcome variables were computed from interaction models. Results: Child marriage is significantly associated with decreased use of institutional delivery care services. Compared to women who married at adult ages (≥18 years), women who married between ages of 12–14 years were the most disadvantaged in having delivered at a health facility (odds ratio [OR]: 0.62; 95% confidence interval [CI]: 0.51–0.74) and having a skilled attendant present (OR: 0.63; 95% CI: 0.53–0.75) at the birth of their last child. The analysis suggests that the effect of education on the use of institutional delivery care is stronger among women married at age 18 or older compared to women who married younger than age 18 years. Further, the joint effect of age at marriage and education is stronger for women living in urban than rural place of residence. Conclusions: Increasing the age at marriage and discouraging child marriage may be a fruitful way to improve mother and child health in Bangladesh. Encouraging girls to complete high school and pursue college education would also help decline the rate of child marriage and, in turn, benefit social mobility and health. Highlights: Child marriage adversely impacts a young mother's life chances and maternal healthcare. Child marriage is associated with lower probability of institutional delivery care services use. Effect of education on delivery care use is greatly weaker for women who married during their childhood. Joint effect of age at marriage and education is stronger for women living in urban areas than rural areas.